Strategi Pengembangan Kacang Hijau Kabupaten Demak Jawa Tengah - Sri Suhartini; Iwan Aminudin; Elpawati Elpawati (Sharia Agribusiness Journal, 2023)
The main production centre for mung beans in Indonesia is Demak Regency. Mung bean in Demak Regency is a plant grown in paddy fields with the methuk system before the rice harvest by spreading the seeds. Mung bean planting is carried out from the end of May, and mung bean production starts from August to November. Mung beans have been planted, used for food and beverage needs, and exported to Asian countries since 2015. Statistical data for 2012-2021 shows an increase in the harvested area of 4.32% and production of 4.88%, but productivity has decreased by 2.30%. This decrease indicates that the development of green beans is not going well. This research was conducted to analyse green bean development strategies and formulate appropriate procedures for implementation in Demak Regency. The IFE and EFE matrices obtained values of 2.612 and 2.958, resulting in an Automatic meeting point in cell V. Based on the SWOT Matrix, the strategy for developing green bean agribusiness in Demak Regency is a hold and maintain or stabilization strategy. QSPM shows that the right approach is to increase the quality of mung beans by increasing the skills of farming actors and using the latest agricultural machinery (Strategy 3). Utilizing the potential of the land in collaboration between Stakeholders for production in other seasons (Strageti 4). Application of cultivation according to technology recommendations by using technology and information to increase production (Strategy 1). Carry out routine maintenance of normalization of irrigation canals to reduce sediment build-up (Strategy 2) Keywords: Mung Bean, IE, SWOT, QSPM AbstrakSentra produksi utama kacang hijau di Indonesia adalah Kabupaten Demak. Kacang hijau di Kabupaten Demak merupakan tanaman yang ditanam di persawahan dengan sistem methuk sebelum panen padi dengan menyebarkan bijinya. Penanaman kacang hijau dilakukan mulai akhir Mei, dan produksi kacang hijau dimulai pada Agustus hingga November. Kacang hijau telah ditanam, dimanfaatkan untuk kebutuhan makanan dan minuman, serta diekspor ke negara-negara Asia sejak tahun 2015. Data statistik tahun 2012-2021 menunjukkan peningkatan luas panen sebesar 4,32% dan produksi sebesar 4,88%, namun produktivitas mengalami penurunan sebesar 2,30% . Penurunan ini menandakan bahwa perkembangan kacang hijau tidak berjalan dengan baik. Penelitian ini dilakukan untuk menganalisis strategi pengembangan kacang hijau dan merumuskan prosedur pelaksanaan yang tepat di Kabupaten Demak. Matriks IFE dan EFE diperoleh nilai 2,612 dan 2,958, sehingga terdapat titik temu otomatis pada sel V. Berdasarkan Matriks SWOT, strategi pengembangan agribisnis kacang hijau di Kabupaten Demak adalah strategi hold and maintain atau pemantapan. QSPM menunjukkan bahwa pendekatan yang tepat adalah meningkatkan kualitas kacang hijau dengan meningkatkan keterampilan pelaku pertanian dan menggunakan mesin pertanian terkini (Strategi 3). Memanfaatkan potensi lahan hasil kerjasama antar Stakeholder untuk produksi pada musim lainnya (Strageti 4). Penerapan budidaya sesuai anjuran teknologi dengan memanfaatkan teknologi dan informasi untuk meningkatkan produksi (Strategi 1). Melaksanakan pemeliharaan rutin normalisasi saluran irigasi untuk mengurangi penumpukan sedimen (Strategi 2) Kata Kunci : Kacang Hijau; IE; SWOT; QSPM